Resveratrol Inhibits Nucleosome Binding and Catalytic Activity of PARP1 - Darya O. Koshkina; Natalya V. Maluchenko; Anna N. Korovina; Angelina A. Lobanova; Alexey V. Feofanov; Vasily M. Studitsky (Biomolecules, 2024)
The natural polyphenol resveratrol is a biologically active compound that interacts with DNA and affects the activity of some nuclear enzymes. Its effect on the interaction between nucleosomes and poly(ADP-ribose) polymerase-1 (PARP1) and on the catalytic activity of PARP1 was studied using Western blotting, spectrophotometry, electrophoretic mobility shift assay, and single particle Förster resonance energy transfer microscopy. Resveratrol inhibited PARP1 activity at micro- and sub-micromolar concentrations, but the inhibitory effect decreased at higher concentrations due to the aggregation of the polyphenol. The inhibition of PARP1 by resveratrol was accompanied by its binding to the enzyme catalytic center and a subsequent decrease in PARP1 affinity to nucleosomal DNA. Concurrent binding of talazoparib to the substrate binding pocket of PARP1, which occurs in the presence of resveratrol, restores the interaction of PARP1 with nucleosomes, suggesting that the binding sites of resveratrol and talazoparib overlap. The data suggest that resveratrol can be classified as a natural inhibitor of PARP1.